Utilizing Participatory Action Research to Foster Effective Family/School Collaboration at an Urban PreK-8 Catholic School - Shriberg, David; Schumacher, Ruth; McMahon, Kara C.; Flores, Sofia; Moy, Gregory E.; Swidzinski, Joanna; Tompkins, Nicole A. (Catholic Education: A Journal of Inquiry and Practice, 2012)
This paper describes a study focused on promoting culturally responsive collaboration practices at an urban preK-8 Catholic school. Using participatory action research (PAR) as its framework, a team of school stakeholders and university faculty and students from the psychology department partnered to create a participant-driven data collection and analysis procedure that culminated in the implementation of a new communication protocol judged by educators and parents to have led to significant improvements in family-school communications. Lessons learned from this experience, particularly as they relate to the use of PAR principles in an urban Catholic school, will be shared.